2012
DOI: 10.1523/jneurosci.4779-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Becoming Consistent: Developmental Reductions in Intraindividual Variability in Reaction Time Are Related to White Matter Integrity

Abstract: Cognitive development is known to involve improvements in accuracy, capacity, and processing speed. Less is known about the role of performance consistency, and there has been virtually no empirical examination of the neural underpinnings of within-person variability in development. In a sample of 92 healthy children and adolescents aged 8 -19 years, we aimed to characterize age-related changes in trial-to-trial intraindividual variability (IIV) of reaction time (RT) and to test whether IIV is related to white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
180
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(201 citation statements)
references
References 73 publications
19
180
2
Order By: Relevance
“…Previous studies have failed to observe a relationship between MRS measures of M1 GABA and intracortical inhibition, measured with paired-pulse TMS protocols using interpulse intervals of 2.5 or 3 ms (Stagg et al, 2011b;Tremblay et al, 2013). Whereas paired-pulse TMS protocols are hypothesized to measure intracortical inhibitory mechanisms, the goal of our study was to explore the relationship between GABA concentrations within M1 and intrinsic corticospinal excitability, not intracortical inhibition.…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous studies have failed to observe a relationship between MRS measures of M1 GABA and intracortical inhibition, measured with paired-pulse TMS protocols using interpulse intervals of 2.5 or 3 ms (Stagg et al, 2011b;Tremblay et al, 2013). Whereas paired-pulse TMS protocols are hypothesized to measure intracortical inhibitory mechanisms, the goal of our study was to explore the relationship between GABA concentrations within M1 and intrinsic corticospinal excitability, not intracortical inhibition.…”
Section: Methodsmentioning
confidence: 93%
“…Spectra were zero-filled from 1024 to 4096 data points, apodized with a 4 Hz Gaussian function, and manually phase corrected and aligned to creatine (Cr; Evans et al, 2013;Near et al, 2015). A combined automated and manual routine was used to identify spectra containing large numbers of extreme values that were excluded from further analysis (Near et al, 2013). The mean percent averages removed (of 64 averages total) was 0.5 Ϯ 0.4% for the LPF, 0.4 Ϯ 0.3% for the M1, 0.3 Ϯ 0.2% for the PM, and none for the OCC voxel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 The reduction of RTV during adolescence has been partially linked to the maturation of white matter tracts in the brain. 20 A recent study performed in young patients with ADHD and healthy controls showed that FA of the left cingulum bundle (CB) was negatively correlated with τ only in patients with ADHD. 13 Importantly, the CB is part of the attentional network model as defined by Makris and colleagues.…”
Section: Introductionmentioning
confidence: 99%